Leadership, Teacher Empowerment, and Change Management: Fostering Transformational Practices in ‘Sekolah Penggerak’ Initiatives - Agus Subagio; Usman Radiana; Luhur Wicaksono (Didaktika: Jurnal Kependidikan, 2024)
The purpose of this article is to explore the intersection of leadership, teacher empowerment, and change management within the framework of the "Sekolah Penggerak" initiative, a transformative educational program in Indonesia. The study examines how leadership practices influence teacher empowerment and the successful implementation of change management strategies in educational settings. Using a qualitative approach, the article highlights the critical role of transformational leadership in fostering a culture of innovation and collaboration among educators. Findings reveal that empowering teachers through participative decision-making, professional development, and supportive environments is key to sustaining change initiatives. The article concludes by offering recommendations for school leaders to enhance the effectiveness of "Sekolah Penggerak" initiatives by prioritizing teacher empowerment and embracing dynamic change management practices to achieve long-term educational reform.